Humic Acid Alleviates Low-Temperature Stress by Regulating Nitrogen Metabolism and Proline Synthesis in Melon (Cucumis melo L.) Seedlings - Libao Zhu; Haihe Liu; Yanping Zhang; Yanxia Cao; Yiwen Hu; Yalun Wang; Haiqiang Zheng; Mengze Liu (Horticulturae)
Melon is a thermophilic crop that is extremely sensitive to temperature changes. Humic acid (HA) is an eco-friendly biostimulant that enhances plants against abiotic stresses. However, the effect of HA on the cold tolerance of melon plants under low-temperature scenarios is still unclear. This study aimed to find out the effects of HA treatment on the morphological, physiological, and nitrogen metabolism of melon seedlings under low-temperature stress. HA treatment significantly enhanced plant height, stem diameter, fresh weight, dry weight, chlorophyll content (up to 33.17%), maximum photochemical efficiency (Fv/Fm), root architecture, superoxide dismutase (SOD), and catalase (CAT) activity. HA also promoted the degradation of nitrate nitrogen (NO3−-N); the synthesis of ammonium nitrogen (NH4+-N), free amino acids, proline, and soluble protein; and nitrogen metabolism (NR, GS, GOGAT, and GDH, up to 181.83%) and proline-related enzyme activity (P5CS and OAT, up to 81.97%). HA significantly increased the expression of nitrogen metabolism and proline metabolism genes. In summary, HA alleviated the damage caused by low-temperature stress by improving levels of antioxidant enzymes, nitrogen metabolism, and proline synthesis.